2019
DOI: 10.31533/pubvet.v13n5a321.1-15
|View full text |Cite
|
Sign up to set email alerts
|

Produtividade de capim Paiaguás sob doses de nitrogênio e cortes

Abstract: Resumo. O objetivo deste trabalho foi avaliar a produção de massa seca e outras características agronômicas da Brachiaria brizantha cv. Paiaguás em diferentes doses de nitrogênio (N), no terceiro ano de produção. O experimento foi realizado na Universidade do Estado de Mato Grosso, em Tangará da Serra -MT, Brasil. O delineamento experimental foi em blocos casualizados (DBC), com seis tratamentos (0, 50, 100, 150, 200 e 250 kg/ha de N) e quatro repetições. Foram realizados quatro cortes e analisadas as variávei… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
3
0
1

Year Published

2019
2019
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 24 publications
0
3
0
1
Order By: Relevance
“…(2019) reported higher forage yields with the application of 200 or 300 kg of N ha -1 at both evaluated defoliation intensities (8, 16 24 and 32 cm above ground). Similarly, Nascimento et al (2019) found a linear effect of nitrogen fertilization on the green biomass yield of B. brizantha cv. Paiaguás with the application of up to 250 kg of N ha -1 .…”
Section: Resultsmentioning
confidence: 79%
“…(2019) reported higher forage yields with the application of 200 or 300 kg of N ha -1 at both evaluated defoliation intensities (8, 16 24 and 32 cm above ground). Similarly, Nascimento et al (2019) found a linear effect of nitrogen fertilization on the green biomass yield of B. brizantha cv. Paiaguás with the application of up to 250 kg of N ha -1 .…”
Section: Resultsmentioning
confidence: 79%
“…However, the use of this fertilizer alone does not guarantee maximum forage production. Several studies have been carried out to access which dose of the nutrient provides maximum productive response of forages (Cabral et al, 2012;Costa et al, 2016;Germano et al, 2018;Teixeira et al, 2018;Nascimento et al, 2019;Sales et al, 2020;Wasselai et al, 2020). In addition, it is important to identify, during the rainy season, which is the most suitable time to carry out fertilization, as well as how many days after defoliation the fertilizer should be applied.…”
Section: Introductionmentioning
confidence: 99%
“…The growth stage at which the plants was harvested directly affects the yield, chemical composition, regrowth capacity and persistence (Dim et al, 2015;Paiva et al, 2019). Cuts or less frequent grazing provide greater forage yields, however, concomitantly decreases occur accented in their chemical composition, with greater deposition of fibrous material, decrease in leaf/stem ratio (Costa et al, 2007;Pereira, 2013;Nascimento et al, 2019). Therefore, one must seek the balance between yield and forage quality, to ensure the nutritional requirements of animals while securing the persistence and productivity of pastures.…”
Section: Introductionmentioning
confidence: 99%